Membrane phase-dependent occlusion of intramolecular GLUT1 cavities demonstrated by simulations - Iglesias-Fernandez, J; Quinn, P; Naftalin, R; Domene, C (Elsevier, 2017)
Experimental evidence has shown a close correlation between the composition and physical state of the membrane bilayer and glucose transport activity via the glucose transporter GLUT1. Cooling alters the membrane lipids from the fluid to gel phase, and also causes a large decrease in the net glucose transport rate. The goal of this study is to investigate how the physical phase of the membrane alters glucose transporter structural dynamics using molecular-dynamics simulations. Simulations from an initial fluid to gel phase reduce the size of the cavities and tunnels traversing the protein and connecting the external regions of the transporter and the central binding site. These effects can be ascribed solely to membrane structural changes since in silico cooling of the membrane alone, while maintaining the higher protein temperature, shows protein structural and dynamic changes very similar to those observed with uniform cooling. These results demonstrate that the protein structure is sensitive to the membrane phase, and have implications for how transmembrane protein structures respond to their physical environment.